Arctic Bay Formation, Borden Basin, Nunavut (Canada): basin evolution, black shale, and dissolved metal systematics in the Mesoproterozoic ocean - KAMBER, BALZ SAMUEL (My University, 2012)
The Arctic Bay Formation (Nunavut, Canada) represents a late Mesoproterozoic muddy terrigenous ramp and contains >200 m of black shale. The formation was studied in order to decipher the tectonostratigraphic and geochemical evolution of the basin, address the origin of metal enrichment, and determine whether this frontier basin has the potential to host sedimentary-exhalative or polymetallic black shale deposits. Samples were analysed in the laboratory for major and trace elements, total organic carbon (TOC), 4-step loss-on-ignition (LOI), and Pb isotopes. Non-calcareous black shale exhibits neither Ce nor Y anomalies, reflecting euxinia in the lower water column, whereas slightly dolomitic black shale has both Ce and Y anomalies, reflecting the dolomite's probable origin as a precipitate in the upper water column. The stratigraphic distribution of the rare earth elements (REEs) indicates an evolving sediment provenance, and Pb isotopic data indicate that the source of clay in the black shale was dominated by weathered, juvenile, mantle-derived material. Base metals and redox-sensitive metals, expressed as enrichment ratios relative to conservative lithophile elements, are elevated and exhibit coherent covariations in the black shale. Enrichment in the redox-sensitive elements, such as Mo and U, correlates with dolomite content of the shale, rather than with organic C or Fepy. From a deep-time ocean evolution perspective, this important observation suggests that enrichment in these metals cannot necessarily be attributed to metal incorporation at an interface between sediment and euxinic water. Instead, in Arctic Bay Formation black shale, the metals were either scavenged onto dolomite as it precipitated in the water column, or secondarily re-distributed within the sediment according to its dolomite content. The base metals that are concentrated in the black shale (e.g., Zn) were probably sourced from diffuse hydrothermal venting, and although there is no evidence at the studied location for a nearby point source of metals (vent), persistent bottom- water euxinia would have ensured the effective scavenging of any dissolved metals supplied, and so the basin has at the very minimum a hypothetical potential for SEDEX and polymetallic mineralisation. Whole-rock U-Th-Pb isotope analysis of black shale yielded a date of 1092 ? 59 Ma, which is considered to be the Arctic Bay Formation's depositional age.
PUBLISHED
Keywords: Geology; Black shale; Geochemistry; Mesoproterozoic; Arctic Bay Formation; Borden Basin